2010
DOI: 10.3166/ga.23.267-285
|View full text |Cite
|
Sign up to set email alerts
|

Assessing human impact on alluvial fan development: a multidisciplinary case-study from Lower Khuzestan (SW Iran)

Abstract: This paper presents a multidisciplinary approach for studying the evolution of an alluvial fan system in Lower Khuzestan (SW Iran). The study draws on previously collected data from geological and archaeological field campaigns and new data derived from the interpretation of satellite imagery and historical textual sources. Three alluvial fans were identified, successively deposited by the Jarrahi river in progressively downstream/westward direction. Judging from archaeological and historical evidence, the suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…The alluvial depositional history of the river Jarrahi and the development of its three spatially separated alluvial fans have been reconstructed in detail (Walstra et al , ). It has been demonstrated that human‐intervention had an important impact on the evolution of the different fans.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The alluvial depositional history of the river Jarrahi and the development of its three spatially separated alluvial fans have been reconstructed in detail (Walstra et al , ). It has been demonstrated that human‐intervention had an important impact on the evolution of the different fans.…”
Section: Resultsmentioning
confidence: 99%
“…Previous case‐studies highlighted the substantial effect of human actions (notably the construction of large‐scale irrigation works) on the river patterns and sedimentation history of the region (Alizadeh et al ; Verkinderen, ; Walstra et al , ; Heyvaert et al , ). This paper is not intended to replicate this work, but rather to re‐evaluate the case‐studies in the light of controls and mechanisms of avulsions, with particular focus on human action.…”
Section: Datasets and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of methods were applied, including field survey (Kavanagh, 2009), geomorphological and sedimentological fieldwork (Goudie et al, 1990;Jones et al, 1999a), and analysis of topographical information, geological maps, and remote sensing images. This included the use of a unified LandsatTM and CORONA database of processed and geo-referenced imagery using ERDAS IMAGINE and ArcGIS ® software (Walstra et al, 2010a(Walstra et al, , 2011. All of the data was compiled and used with data from previous work in the region to demarcate areas of human activities, structural geology, and river characteristics which included river hydrology, sedimentology, morphology, migration, and longitudinal profiles.…”
Section: Methodsmentioning
confidence: 99%
“…Other factors, such the constraining influence of the River Jarrahi delta to the east (Fig. 7), may have been more influential in the persistence of this near-straight river course (Walstra et al, 2010a;Heyvaert et al, 2013).…”
Section: Interactions Between Major Anthropogenic River Channel Straimentioning
confidence: 96%